South-south cooperation: a case study of contemporary Sudanese Malaysian relations - Abdel Salam, El Fatih Abdullahi; Eissa, Garoot Suleiman; Omar, Muhamad Fuzi (2015)
South-South Cooperation is a term historically used by policymakers to refer to the exchange of resources, technology and knowledge between developing nations; also known as nations of the global south. Leaders of the South hope that this new cooperation will bring a new World Order to counter the existing Western social, economic and political dominance. This paper examines and analyses Sudanese- Malaysian relations during the last few decades as a typical example of that cooperation. It offers a comprehensive description, analysis and evaluation of the relations between these two countries with emphasis on the diplomatic, economic and cultural spheres of these relations. In addition, it undertakes an adequate survey of the historical evolution of relations. An historical but analytical methodology will be employed. Information sources for this paper includes primary and secondary sources comprising: archival materials, documents, books and statistical data sources particularly in the economic and cultural spheres. Examination of bilateral relations highlights the predominance of the economic factor as the major determinant of relations. Diplomatic relations between the two countries go back to the 1970s; yet it was only in the late 1980s and early 1990s that they witnessed rapid promotion. The Isolation imposed on Sudan due to its pan-Islamic discourse was the most important factor that forced Sudan to ‘look east’ and reorient its economic and cultural ties towards Asian countries, particularly China and Malaysia. Sudan’s ties with Malaysia resulted in steadily growing relations between the two countries resulting in increasing levels of trade and significant amount of investment particularly in the crude oil field. By virtue of it Sudan has successfully started and sustained its oil exploration and exportation project mainly with Malaysian finance and technology. Politically the two countries show identical views on different regional and international issues. Culturally, more and more students are coming from Sudan to study in Malaysia and vice versa. This paper will conclude by suggesting specific policy recommendations to help boost and bolster the bilateral relations between the two countries. It will also highlight the point that South-South relations in general can be a promising approach on the way towards sustained development. Implications of findings for theory will be highlighted. Key Words South-South cooperation, political relations, economic relations, PETRONAS, foreign policy